2021
DOI: 10.1111/jocs.15291
|View full text |Cite
|
Sign up to set email alerts
|

Percardiac closure of large apical ventricular septal defects in infants: Novel modifications and mid‐term results

Abstract: Background/Aim Both open heart surgery and percutaneous approaches retain several limitations in closing large apical muscular ventricular septal defects (AmVSD) in infants. We present probe‐assisted percardiac device closure (PDC), an exclusively transoesophageal‐echocardiography guided technique, as an alternative with midterm results. Methods Thirty‐six infants with large AmVSDs (single or multiple‐holed) underwent PDC in our department. Mean AmVSD for single and multiple‐holed measured 7.2 ± 2.4 mm and 6.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Zhu's research has shown that for patients with permanent pacemaker implantation whose basal state LVEF is reduced (≤40 %-45 %) or who have been followed up for >1 y, RVNA pacing has less impact on postoperative LVEF than RVA pacing. The conclusions are similar [32,33] .…”
Section: Resultssupporting
confidence: 59%
“…Zhu's research has shown that for patients with permanent pacemaker implantation whose basal state LVEF is reduced (≤40 %-45 %) or who have been followed up for >1 y, RVNA pacing has less impact on postoperative LVEF than RVA pacing. The conclusions are similar [32,33] .…”
Section: Resultssupporting
confidence: 59%
“…Closure of apical VSDs in infants is challenging for surgeons and interventional cardiologists. Although a hybrid approach has been used for some time, Changwe et al 2 describe a novel surgical technique to close apical VSDs that uses a probe‐assisted delivery system. This is done through a chest incision with the aid of transesophageal echocardiography.…”
mentioning
confidence: 99%